On How People Navigate Through Their Personal Web of Things - Eswaran, Dhivya; Iqbal, Shamsi; Fourney, Adam; Williams, Shane; Bennett, Paul (CHI 2020 Workshop on Speculative Designs for Emergent Personal Data Trails, 2020)
In a digital setting, people accomplish their goals by interacting with multiple files, web pages, emails, and applications – each of which often relates to multiple projects and people. This leads to a rich interconnected personal web of things, comprising heterogeneous entities and information interaction trails. In this work, we seek to understand a single dimension of the personal web in work-related settings, namely, how people transition between activities. To this end, we develop an instrumentation platform to log all activities that a person performs across all desktop applications (e.g. web browsers, editors and email clients). With the goal of understanding how people’s transition across activities relate to their productivity, we conduct a study involving ten participants to collect logs of activities performed by them on their primary work devices over a 4-5 week duration. Our analysis of this data provides an initial insight into people’s behavior in this space, which envelops personal corpora (e.g. emails, documents), public resources accessed (e.g. webpages), and activities undertaken across multiple applications. We conclude by outlining how our observations can be leveraged to provide better productivity support, and more broadly, the rich set of technical questions and challenges the personal web setting poses for exciting future research.